O mundo sem telas: corpo, tecnologias digitais e a biopolítica do tocar - Jesus, Igor Maximiliano de (2016)
Recent technological launchings show us an important change in the relation between media and body, announcing a communicational quotidian no longer based on screen hegemony. Body increasingly acquires centrality in the digital communication and senses which did not receive proper attention, such as touch, are more and more requested by the technological advances that have been developed and researched in the past years. Cognitive changes brought about by this encounter are profound and yet not really thoroughly known. Before such a problem, technologies that presently inaugurate and announce this communicational moment are the unit of analysis – touchscreens, virtual reality releases, projects like Cicret Bracelet, Soli, Jacquard, and specific cases such as the one of cyborg Evgeny Chereshnev. They are all analysed with a view to testing the hypothesis that the inherent biopolitics in the sense of touch is the key to understanding the above-mentioned cognitive changes that mark out behaviour and subjectivity, since it is clear that the new relevance of this sensory dimension has been triggered by touchscreen technologies and taken forward by the World without the Screens that we currently know (Katz, 2015a). The objective pursued is to identify the cognitive and sociocultural aspects that come to light due to our intimate contact with digital media, as well as to reflect on the approximation between technologies and body, from the perspective of the relevance of touch in contemporary communication. The significance of this investigation is given by the transition moment that we find ourselves in towards a world where screens get closer and closer to body – a phenomena that also occurs when we observe the functioning of other emerging digital technologies. In order to theoretically support what we propose we rely on the works of Carr (2011), Cranny-Francis (2013), Greiner and Katz (2001, 2005, 2010, 2015), Katz (2015a, 2015b), Manovich (2013), Mandary and Metzinger (2016), Montagu (1988), Rose (2014), and others, according to a methodology that takes into account a literature review and essentially qualitative data